Perbandingan Tingkat Kepatuhan Pengobatan Pasien Epilepsi antara Monoterapi dan Politerapi di Poliklinik Saraf RSUP Dr. M. Djamil Padang - Hendra Permana; Elsi Rahmadhani Hardi (Universitas Baiturrahmah, 2021)
Background: Epilepsy is one of the most common chronic neurological disorders affecting people worldwide. People with epilepsy have higher mortality rate than general population. Medication adherence is predictor for epilepsy outcome. Number of medication is one of contributing factors to therapy adherence. Aims: to determine antiepileptic drug adherence between monotherapy and polytherapy at Neurology Clinic Dr. M. Djamil Hospital. Methods: This study conducted at Neurology Clinic Dr. M. Djamil Hospital from May to June 2019. Medication adherence was assessed by using Morisky Medication Adherence Scale (MMAS) 8. Data was analyzed and level of significance was if p value ≤ 0.05. Result: We recruited 30 participants which consist of 14 (46.7%) female and 16 (53.5%) male. Median of age 31 (13-77) and 22 (73.3%) patients have high educational level. From 30 patient, 14 (46.7%) in monotherapy and 16 (53.3%) in polytherapy. Patient with high medication adherence 4 (13.3%), moderate 7 (23.3%) and poor 17 (56.7%). Statistical analysis showed no differences on medication adherence between monotherapy and polytherapy (p=0.79). Conclusion: There are no differences on medication adherence between monotherapy and polytherapy at Neurology Clinic Dr. M. Djamil Hospital.